Modular hybrid total hip arthroplasty. Experimental study in dogs - Minto, Bruno W. [UNESP]; Brandão, Claudia Valeria Seullner [UNESP]; Pereira, Gilberto J. C. [UNESP]; Campagnol, Daniela [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Padovani, Carlos Roberto [UNESP]; Ranzani, José Joaquim Titton [UNESP] (Biomed Central Ltd., 2011)
Background: This prospective experimental study evaluated the surgical procedure and results of modular hybrid total hip arthroplasty in dogs.Methods: Ten skeletally mature healthy mongrel dogs with weights varying between 19 and 27 kg were used. Cemented modular femoral stems and uncemented porous-coated acetabular cups were employed. Clinical and radiographic evaluations were performed before surgery and at 30, 60, 90, 120, 180 and 360 days post-operation.Results: Excellent weight bearing was noticed in the operated limb in seven dogs. Dislocation followed by loosening of the prosthesis was noticed in two dogs, which were therefore properly treated with a femoral head osteotomy. Femoral fracture occurred in one dog, which was promptly treated with full implant removal and femoral osteosynthesis.Conclusions: The canine modular hybrid total hip arthroplasty provided excellent functionality of the operated limb.
Keywords: Dog; hip; total hip prosthesis; hybrid system; modular system